(untitled) (TAJ: Journal of Teachers Association, 2018)
Caesarean myomectomy which had traditionally discouraged in the past has recently been frequently employed to remove myoma at the time of caesarean section. If myomectomy during caesarean section become a wide spread practice, it could potentially be eliminate multiple surgeries for both indications. Objective of the study was to evaluate the safety and feasibility of performing myomectomy during caesarean section. Methods: This was a prospective study done in different private clinics in Rajshahi City from January 2012 to January 2015. Total 20 pregnant women with different sized fibroids were included in this study. Patients evaluated by age, parity, gestational age, difficulties during operation, blood loss during surgery, per and post-operative complications. Results: Blood loss during surgery was 750-1000 ml in 10 (50%) patients. Fifteen (75%) patients needed blood transfusion. The maternal morbidities like anaemia, pyrexia, and sepsis developed in 2(10%) of cases. There was no maternal or perinatal mortality. Conclusion: With the advent of better anesthesia and availability of blood, caesarean myomectomy is no longer a dreaded job in the hands of a skilled obstetrician in a well-equipped tertiary hospital. TAJ 2017; 30(1): 27-29